Cationic BPI-gold(III) complexes: controlling ligating and nonligating anions - Roth, Torsten; Wadepohl, Hubert; Gade, Lutz H. (European journal of inorganic chemistry, 2016)
Abstract A new synthetic protocol has been devised to access cationic gold(III) bis(2-pyridylimino)isoindolato (BPI) complexes. The rigid BPI framework was shown to stabilize this type of coordination compound and allowed different substitution patterns in the ligand periphery. The synthesis of these complexes tolerates both air and moisture and does not require transmetalation steps with toxic thallium or mercury compounds. Notably, control of the counterion was achieved through the use of an ion-exchange resin and salt metathesis. The selective modification and transformation of the anionic ligand in the fourth coordination site of the square-planar complexes was studied while leaving the noncoordinated counterion unchanged. Such transformations, which are of importance in the coordination chemistry and catalysis of gold(III) complexes, proved to be very selective, provided that the ligating and nonligating anionic species where sufficiently different in nature. In all cases, strict N,N,N-coordination of the BPI scaffold was found, thus conserving the C2v symmetry of the square-planar complexes.
Gesehen am 05.05.2020